Cross-Linked αsγt-Chain Hybrids in Plasma Clots Studied by 1D- and 2D Electrophoresis and Western Blotting - Grøn, B; Filion-Myklebust, C; Bjørnsen, S; Haidaris, P; Brosstad, F (Thrombosis and Haemostasis, 1993)
Fibrinogen and fibrin related chains in reduced human plasma as well as the bonds interlinking partially cross-linked fibrin from plasma clots have been studied by means of 1D- and 2D electrophoresis and Western blotting. Immunovisualization of reduced plasma or partially cross-linked fibrin with monoclonal antibodies specific for the α-chains or the γ-chains have shown that several bands represent material belonging to both chains. In order to decide whether these bands constitute αγ-chain hybrids or superimposed α- and γ-chain dimers, the cross-linked material was separated according to both isoelectric point (pI) and molecular weight (MW) using Pharmacia’s Multiphor II system. Western blotting of the second dimension gels revealed that partially cross-linked fibrin contains αsγt-chain hybrids and γ- polymers, in addition to the well-known γ-dimers and α-polymers. The main αsγt-chain hybrid has a pI between that of the α- and the γ-chains, a MW of about 200 kDa and contains Aα-chains with intact fibrinopeptide A (FPA). It was also observed that soluble fibrinogen/fibrin complexes as well as partially cross-linked fibrin contain degraded α-dimers with MWs close to the γ-dimers. These findings demonstrate that factor XIII-catalyzed cross-linking of fibrin is a more complex phenomenon than earlier recognized.